Diagnostic laparoscopy in the evaluation of female factor infertility - K., Ashok Kumar; Y., Priyanka Jogi; Anjanappa, Bharathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Infertility is a global problem, with more than 70 million couples suffering every year. In India 10-15% of populations are suffering from infertility. All these people need accurate diagnosis and treatment. Among the many investigations available to evaluate the female partner of the infertile couples, laparoscopy is relatively recent and considered gold standard for pelvis evaluation. The objective of the study was to study the different causes of female factor infertility with diagnostic laparoscopy. Methods: This is a prospective study done on 50 infertile females who attended infertility clinic of department of OBG, ESIC MC and PGIMSR, Rajajinagar, Bengaluru from September 2013 to 2015. Both primary and secondary infertility females were included in this study. These patients underwent diagnostic laparoscopy in premenstrual phase (7, 8, 9th day of menstrual cycle) after conducting thorough clinical and biochemical examinations. Results: In the present study total 50 infertility cases were included. 41 cases had primary infertility and 9 cases had secondary infertility. Mean age was 29.88 years and mean duration of infertility was 5.9 years. Abnormal laparoscopic findings were detected in 41 (82%) cases. Tubal factor was seen in 14 (28%) cases, 11 (22%) cases had endometriosis, 10 (20%) cases had ovarian factor, 4 (8%) cases had pelvic adhesions and 2(4%) had fibroid uterus. Conclusions: Tubal factor is the commonest cause for infertility followed by endometriosis and ovarian factor. Diagnostic laparoscopy is the gold standard procedure to assess tubal status. Laparoscopy has a better role than ultrasonography in diagnosing endometriosis and pelvic adhesions.